Consequences and Implications of Anthropogenic Desalination of Salt Marshes on Macrobenthos. Issue 1 (13th November 2015) - Li, Shanze; Cui, Baoshan; Xie, Tian; Shao, Xiaojing; Zhang, Menglu
Abstract : Coastal wetlands are important natural habitats. Wetland restoration and creation projects are often conducted, in part to mitigate for habitat loss, but the factors leading to the success of such projects are not fully understood. A management project was examined in the Yellow River Delta Natural Nature Reserve where large impounded salt marshes were flooded with freshwater with the goal of creating fresh marsh habitat. Areas flooded with freshwater had greater water depth, lower salinity, and bulk density, and more porous and softer soils than unmanipulated areas. The freshwater plant Phragmites australis replaced the salt marsh species Suaeda salsa and Tamarix chinensis at high elevations, but flooding with freshwater led to an extinction of plants at middle elevations. Freshwater flooding reduced densities and the diversity of macrobenthos in high marsh, and macrobenthos were almost absent in the middle marsh. There was no overlap of macrobenthic species between treated and control areas, and the macrobenthic species richness in treated areas was very low. The results suggest that this management technique is more likely to achieve its goals at higher marsh elevations. The success of future projects may be improved by selecting high elevation sites or improving techniques to better reduce salinities in middle elevation sites. As the project replaced salt marshes with fresh marshes that are only partially functional, future projects of this type should only proceed after identifying better techniques that will produce better results. Abstract : A management project is examined in the Yellow River Delta Natural Nature Reserve where large impounded salt marshes are flooded with freshwater with the goal of creating fresh marsh habitat. Areas flooded with freshwater has great changes in water depth and salinity, and further greatly altered the macrobenthic community. The results illustrate the importance of considering water depth and salinity in making future management decisions in coastal wetlands.